2020
DOI: 10.21203/rs.3.rs-58663/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison Between Less Invasive Surfactant Administration (LISA) and Intubation-Surfactant-Extubation (InSurE) in Preterm Infants with Respiratory Distress Syndrome: A Retrospective Study

Abstract: Background: Bronchopulmonary dysplasia (BPD) is an important morbidity caused by neonatal lung injury due to mechanical ventilator use. Respiratory distress syndrome (RDS) is leading cause of mechanical ventilation in preterm infants. Surfactant was administrated through the endotracheal tube for management of RDS, which compels invasive mechanical ventilation. Recently, Intubation-SURfactant administration-Extubation (INSURE) and Less-invasive surfactant administration (LISA) have been introduced to avoid inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 23 publications
3
4
0
Order By: Relevance
“…This could be attributed to similar rate of mechanical ventilation in both the groups. Similar findings were reported from other studies 25–28,31,32 . We found no significant difference in other secondary outcomes such as IVH, NEC, ROP, hsPDA, pneumothorax, and LOS between the groups.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This could be attributed to similar rate of mechanical ventilation in both the groups. Similar findings were reported from other studies 25–28,31,32 . We found no significant difference in other secondary outcomes such as IVH, NEC, ROP, hsPDA, pneumothorax, and LOS between the groups.…”
Section: Discussionsupporting
confidence: 91%
“…As with our study, several other trials 25–32 found no significant difference between the InSurE and LISA groups about the need for intubation within 72 h of birth. Mohammadizadeh et al 26 conducted a multicentre RCT in Iran among 38 preterm babies below 34 weeks gestational age and found insignificant difference in the need for intubation within first 72 h of life.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations